Inferior alveolar nerve relocation and immediate dental implant placement in severely resorbed mandibles: a prospective clinical case series - Hwaiti, Hisham Suliman; Al-Rubidi, Yasser Ahmed; Al-Ashwal, Ahmed; Al-Hadi, Yahya; Al-Kibsi, Taghreed; Al-Wesabi, Mohammed Ali (Springer Science and Business Media LLC, 2025)
Background: Evaluation of neurosensory disturbances (ND) and the success rate of dental implants related to inferior alveolar nerve lateralization (IANL) and immediate dental implant placement in the posterior atrophic mandible. Methods: A prospective clinical case series was conducted among five edentulous patients with posterior mandibular atrophy. The study included 9 IANL sites. Nerve function and implant success rate were assessed during follow-up. Differences between pre- and post-operative outcomes were analyzed. Results: The study included patients aged 24-72 years, with a mean age of 56.22 ± 16.49 years and a male predominance (77.7%). Surgical procedures were performed on the right side in 55.56% of cases and on the left side in 44.44%. By one month, 44.4% reported full recovery, 33.3% reported moderate hypoesthesia, and 22.3% had mild hypoesthesia. At three months, 33.3% had full recovery, 55.6% experienced mild hypoesthesia, and 11.1% (1 patient) reported anesthesia. At six months, 88.9% had recovered, with only one patient (11.1%) still reporting anesthesia. A statistically significant difference in ND was observed across follow-ups at day one, week one, month one, month three, and month six (χ² = 30.3, p < 0.001). Pairwise comparisons revealed significant improvements from day one to month one (p = 0.03), day one to month three (p = 0.008), and day one to month six (p = 0.005), while the difference between day one and week one was not significant (p = 1.00). No significant correlations were found between ND recovery and patient age or membrane type at any follow-up interval (p > 0.05). Conclusion: The study showed that IANL with immediate implant placement is an effective technique for rehabilitating atrophic posterior mandibles. Trial registration: The study protocol has been registered in ClinicalTrials.gov (Identifier NCT07104994, 5/8/2025), and the date of registration was retrospectively determined.
Keywords: Alveolar ridge resorption; Dental implant; Inferior alveolar nerve lateralization; Mandibular atrophy